Analisis Butir Soal Instrumen Tes Kemampuan Berpikir Kritis Siswa Pada Tema Usaha Kuliner Penerapan Materi Suhu dan Kalor - Mahmudah, Novi Rif'atul; Setyarsih, Woro (Universitas Negeri Surabaya, 2024)
One of the 21st century life skills that a person must develop and train through the educational process to be successful in life is the ability to think critically. Critical thinking is a skill that includes observation, analysis, interpretation, reflection, evaluation, inference, explanation, problem solving, and decision making. The aim of this research is to analyze the validity and reliability of critical thinking ability test instruments using descriptive analysis. This research was conducted at one of the state high schools in the city of Surabaya. The population in this study was 30 students. Students' critical thinking abilities were measured using test questions from the preparation of critical thinking test instruments on temperature and heat material with 12 questions in the form of a presentation. The results of this research were that the validity of the question items obtained a value of 0.341 to 0.751 with the information that 11 questions were declared valid and one question item was invalid. Then, the reliability of the instrument developed was obtained by a calculated r of 0.804 with the instrument statement being declared reliable. Thus, the instrument developed can be declared valid and reliable as a good test instrument..